CONCEPTUAL PRINCIPLES OF THE PROCESS OF EVALUATING THE EFFICIENCY OF INTEGRATION PROCESSES (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
In the conditions of increasing turbulence in world politics and economy, the analysis of effective integration associations from the point of view of identifying the best practices of cooperation becomes especially relevant. International integration processes are dynamic and constantly evolving. The number of integration entities and agreements is growing every year, which indicates an active movement in the direction of deeper cooperation between the countries. New partnerships, negotiations and creation of regional blocs - all these processes are parts of this evolutionary process. When analyzing the effectiveness of integration structures, it is necessary to take into account both current and potential political problems that can significantly complicate the processes of economic cooperation and the achievement of declared goals. The processes of economic integration take place both bilaterally and on a regional or global basis. A characteristic feature of integrations can now be called their development at the regional level: the creation of a coherent regional economic complex with unified supranational and intergovernmental authorities. economic integration creates good relations between countries in the process of free movement of goods, services, capital and labor, as well as mutual understanding in the field of economics, politics, legislation, and also ensures the exchange of information, etc. Therefore, the stages of development of integration depend on the level of political and economic consensus and the interests of the participants. In general, participation in integration groups, as a rule, has a positive effect on the economies of participating countries. An integration association, characterized by a large market, increases the expected benefit from investments and reduces the risks associated with the sales market, which allows to reduce costs with the help of the growth of potential consumers. Increased competition stimulates the development of more efficient industries, which contributes to the competent allocation of resources. It is noted that it is difficult to objectively assess the effectiveness of integration processes. Currently, there is no single methodology that allows for an accurate assessment of all the effects of integration. It is emphasized that participation in this or that association may have different effects on different participating countries of the same bloc.
Keywords: integration; process; countries; association; structure